2000
DOI: 10.1046/j.1460-9568.2000.00170.x
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of circadian firing rhythms in cultured rat suprachiasmatic neurons

Abstract: The circadian clock in mammals is located in the suprachiasmatic nucleus (SCN) which consists of multiple oscillating neurons. Integration of the cellular oscillations is essential for the generation of a single circadian period in the SCN. By using a multielectrode dish (MED), we measured circadian firing rhythms in individual SCN neurons for more than 2 weeks continuously, and examined the involvement of synaptic communication in the synchronization of circadian rhythms. Cross-correlation analysis of spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
94
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 35 publications
(49 reference statements)
10
94
1
1
Order By: Relevance
“…Mechanisms for synchronization between SCN neurons may be nonsynaptic (22) or synaptic (14). Nonsynaptic synchronization may involve electrical coupling via gap junctions and ionic mechanisms (22)(23)(24) or paracrine factors such as nitric oxide (25), whereas synaptic coupling may involve ␥-aminobutyric acid (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms for synchronization between SCN neurons may be nonsynaptic (22) or synaptic (14). Nonsynaptic synchronization may involve electrical coupling via gap junctions and ionic mechanisms (22)(23)(24) or paracrine factors such as nitric oxide (25), whereas synaptic coupling may involve ␥-aminobutyric acid (26).…”
Section: Discussionmentioning
confidence: 99%
“…After dissociation, isolated SCN neurons express circadian rhythms in their firing patterns (12,13). The freerunning periods of the individual neurons vary from 20 to 28 h. The average period matches the behavioral activity pattern of Ϸ24 h. In these cultured dispersals, synaptically coupled neurons can sometimes be observed with synchronized firing patterns (14). In SCN tissue explants cultured on multielectrode plates, the variation in free-running period is considerably smaller (15)(16)(17).…”
mentioning
confidence: 97%
“…For example, a previous analysis of the role of GABA in SCN neurons in culture found that blocking GABA receptors alters the firing rate and precision of the neural activity rhythms but does not impair synchrony or rhythmicity of the population (Aton et al, 2006). However, previous work has also shown that exogenously applied GABA can phase shift the rhythms in electrical activity (Tominaga et al, 1994;Shirakawa et al, 2000) and can synchronize the population of cellular oscillators in culture (Liu and Reppert, 2000). The GABAergic excitation described in the present study is likely to have a robust impact on how dorsal SCN neurons respond to afferent input.…”
Section: Functional Significance Of Gabaergic Excitationmentioning
confidence: 99%
“…Early work suggested that GABA could evoke excitatory responses during the day (Wagner et al, 1997), but the generality of this finding has been questioned by other laboratories (Gribkoff et al, 1999;De Jeu and Pennartz, 2002). Functionally, the exogenous application of GABA can synchronize the electrical activity of SCN neurons (Liu and Reppert, 2000;Shirakawa et al, 2000); however, GABAergic signaling does not appear to be required for cultured SCN neurons to remain synchronized (Aton et al, 2006). Intriguingly, there is evidence to suggest that GABA-mediated mechanisms are responsible for coupling ventral and dorsal cell populations in the SCN (Albus et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Ces résultats viennent en appui de données, obtenues in vitro, démontrant que les rythmes de sécrétion d'AVP et de VIP peuvent être découplés [37,38]. Chaque NSC serait donc, hypothétiquement, composé de deux oscillateurs couplés.…”
Section: Combien D'horloges Dans Les Nsc?unclassified